Meningkatkan Visibilitas Online UMKM: Pendampingan Pemanfaatan Akun Google Bisnis sebagai Alat Pemasaran untuk Hace Craft Desa Bandar Lor, Kota Kediri - Nuzula, Allieda Firdausi; Phamungkas, Alwy Bayu; Silva, Alyssa Agistiana; Mutamimah, Ana Nur Oktavia; Fadhilah, Amalia Nur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to improve the marketing and promotion of Hace Craft MSMEs, which are located in Bandar Lor Village, Kediri City, East Java, through assistance in utilizing Google Business Accounts. The service method was carried out by Group 2 sharia business practice interns from the Sharia Accounting study program at IAIN KEDIRI, East Java. This activity includes the initial information stage, discussion, account creation, and handover to the business owner. The result was the successful creation of a Google Business Account for Hace Craft, which could then be used as a marketing and promotional medium. Through this assistance, it is hoped that MSME Hace Craft can expand its marketing reach, increase its brand visibility, and reach more customers through a wider and more effective digital platform.